Efficacy and safety of switching from febuxostat to dotinurad, a novel selective urate reabsorption inhibitor, in hyperuricemic patients with type 2 diabetic kidney disease: Protocol for a single-arm, open-label, prospective, exploratory study - Osonoi, Takeshi; Saito, Miyoko; Hosoya, Mitsuru; Douguchi, Satako; Ofuchi, Kensuke; Katoh, Makoto (Frontiers in Endocrinology, 2023)
Background Dotinurad is a novel uricosuric drug in Japan with selective and potent urate transporter 1 (URAT1) inhibitory activity. This study aims to evaluate the efficacy and safety of dotinurad in hyperuricemic patients with type 2 diabetic kidney disease by comparing serum levels of urate and plasma and urinary levels of indoxyl sulfate excreted via the urate excretion transporter ATP binding cassette subfamily G member 2 (ABCG2), as indices, with baseline levels after switching from febuxostat to dotinurad. Methods This single-center, single-arm, open-label, prospective, exploratory study aims to evaluate the effect of switching from febuxostat to dotinurad on serum urate levels and its background factors. The study will include 50 hyperuricemic patients with type 2 diabetic kidney disease and urate levels exceeding 6 mg/dL despite administration of febuxostat 20 mg/day for at least 3 months. The primary outcome is the achievement rate of serum urate levels of ≤6 mg/dL after 24 weeks of treatment with dotinurad at 0.5 mg to a maximum of 4 mg once daily. Secondary outcomes include the changes in serum urate levels, plasma and urinary indoxyl sulfate levels, and renal injury-related markers from baseline to observation points at weeks 4, 12, and 24. Discussion The study hypothesizes that switching to dotinurad may reduce the plasma levels of indoxyl sulfate and increase its urinary levels in patients with hyperuricemia. These suggest that dotinurad can potently lower the serum urate level by inhibiting URAT1 without adversely affecting ABCG2. Thus, findings of this study are expected to provide useful insights into the treatment of hyperuricemia associated with type 2 diabetic kidney disease and the discovery of new possibilities for dotinurad. Ethics and Dissemination Prior to the study, its study protocol was scientifically and ethically reviewed and approved by the Japan Physicians Association Clinical Research Review Board (approval number: JPA007-2204-02). In addition, patients who provide written informed consent will participate in the study. The results of this study will be published through submission to a peer-reviewed scientific journal. Clinical trial registration https://jrct.niph.go.jp/en-latest-detail/jRCTs031220080, identifier jRCTs031220080.